Modern possibilities of minimally invasive methods of diagnosis and treatment in China - Kuo Chen; Le Zhang (Опухоли женской репродуктивной системы)
Breast cancer is now the most common cancer that threatens the health of women in China. The annual number of new cases of breast cancer and the number of deaths in China is 12.2 and 9.6 % respectively of the total amount in the world. Following the scientific and technological progress in the development direction of surgery for breast cancer has been the development in the field of endoscopic surgery, this treatment method with little section provides a good therapeutic result. Along with the aesthetic appearance of cure is achieved at the site of surgery and minimizing the trauma. In China use system “Mammotome” and dustoscopic for preoperative biopsy; and through mastoscopic do breast-conserving surgery, operations mastectomy in breast cancer and reconstruction, sentinel lymph node biopsy, and axillary lymph node dissection; ablation. In China now fully implemented the treatment of breast cancer minimally invasive techniques which is the general trend of the development of surgery in the country.